Analisis Daya Ledak Tungkai, Kecepatan Lari Dan Panjang Tungkai Terhadap Kemampuan Lompat Jauh Siswa SMA Negeri 2 Watampone Kabupaten Bone - Mardiana Mardiana (Universitas Negeri Makassar, 2017)
This study aims to find out how much the value of the contribution of explosive limb power to the ability of long jump, to find out how much the value of the contribution of running speed to the ability of long jump, to find out how much value of long leg contribution to the ability of long jump and to find out how much the value of power contribution limb explosion, running speed, leg length jointly to the ability of long jump student SMA 2 Watampone districk Bone. This type of research uses correlational descriptive method. The population of this study were all students of SMA Negeri 2 Watampone districk Bone which amounted to 532 people. However, the population is restricted to boys only to be homogeneous or have similar characteristics. The sample of this study as many as 60 people drawn at random from the population using the lottery technique. Data collection techniques used were limb power test, running speed test, limb length test, and long jump ability test. Data analysis techniques used are descriptive and inferential statistical analysis techniques with simple regression analysis, and for testing the hypothesis used a simple regression and correlation test to determine the contribution of independent variables to the dependent variable. data processing research in testing hypothesis used computer program SPSS version 15.0. The conclusion of research result indicate that (i) Contribution value of Explosive Limb Ability of long jump student SMA Negeri 2 Watampone districk Bone equal to 69%, with significance level 0.000 <α 0.05. (Ii) Contribution value of running speed to ability of long jump student of SMA Negeri 2 Watampone districk Bone of 52%, with a significance level of 0.004 <α 0.05. (Iii) The value of long limb contribution to the ability of long jump students SMA Negeri 2 Watampone districk Bone at 30%, with a significance level of 0.000 <α 0.05.